2020
DOI: 10.1038/s41598-020-73425-1
|View full text |Cite
|
Sign up to set email alerts
|

Study in circular auxetic structures for efficiency enhancement in piezoelectric vibration energy harvesting

Abstract: Piezoelectric (PZT) components are one of the most popular elements in vibration sensing and also energy harvesting. They are very well established, cost effective and available in different geometries however there are still several challenges in their application particularly in vibration energy harvesting. They are normally narrow-band elements and work in high-frequency range. Their efficiency and power extraction density are also generally low compared with different electromagnetic techniques. Auxetic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 53 publications
0
27
0
2
Order By: Relevance
“…The direct mechanical wear between triboelectric materials leads to TENG devices' poor stability with unstable outputs. Studies have shown that increasing the porosity of materials and decreasing the effective Young's modulus make the triboelectric materials more deformable and increase the effective contact area, resulting in an improved TENG performance and mechanical stability, 94,119,145,146,157 through introducing 3D printed metastructure, [158][159][160] auxetic structures, [161][162][163] and so forth. For instance, Matlack et al 158 suggested that the 3D-printed meta-structure with embedded resonators could not only reduce the overall mass of the device but also expand and reduce the Bragg gap, which has a unique advantage for the absorption of low-frequency vibration energy.…”
Section: Engineering Mechanical Properties Of the Triboelectric Layersmentioning
confidence: 99%
“…The direct mechanical wear between triboelectric materials leads to TENG devices' poor stability with unstable outputs. Studies have shown that increasing the porosity of materials and decreasing the effective Young's modulus make the triboelectric materials more deformable and increase the effective contact area, resulting in an improved TENG performance and mechanical stability, 94,119,145,146,157 through introducing 3D printed metastructure, [158][159][160] auxetic structures, [161][162][163] and so forth. For instance, Matlack et al 158 suggested that the 3D-printed meta-structure with embedded resonators could not only reduce the overall mass of the device but also expand and reduce the Bragg gap, which has a unique advantage for the absorption of low-frequency vibration energy.…”
Section: Engineering Mechanical Properties Of the Triboelectric Layersmentioning
confidence: 99%
“…The new concept of enhancing efficiency of energy harvesting devices is the auxetic resonator-based model presented by Eghbali et al 71 The model consists of a quarter wavelength tube as well, over which the cantilever of the auxetic substrate and plain plate is mounted Figure 25. In this article, the analysis of plain and cellular auxetic plates is observed.…”
Section: Auxetic Resonator-based Approachmentioning
confidence: 99%
“…Figure 25. Plain cantilever is mounted over the quarter wavelength tube and auxetic plate cantilever 71. …”
mentioning
confidence: 99%
“…Salah satu bentuk memanen energi yang aktif dilakukan adalah dengan Penulis Korespondensi: Telp : +62-813-1370-4872 e-mail : koes_kusnandar@yahoo.com memanfaatkan getaran. Konversi energi getaran menjadi energi listrik dilakukan melalui tiga metode populer yaitu elektromagnetik, triboelektrik, dan piezoelektrik (Eghbali et al, 2020). Diantara ketiga metode tersebut, piezoelektrik paling banyak digunakan untuk memanen energi getaran.…”
Section: Rancang Bangun Purwarupa Energy Harvesting Menggunakan Piezo...unclassified
“…Diantara ketiga metode tersebut, piezoelektrik paling banyak digunakan untuk memanen energi getaran. Namun demikian, masalah efisiensi dan daya yang relatif kecil menjadi tantangan dalam membangun pemanen energi berbasis piezoelektrik (Varadha & Rajakumar, 2018;Eghbali et al, 2020;Wang et al, 2020). Beberapa penelitian telah dilakukan dalam konteks pemanenan energi getaran menggunakan piezoelektrik (Afif & Rini, 2017;Büyükkeskin et al, 2019;Nechibvute et al, 2012;Niasar et al, 2020;Pratama dkk., 2015;Xu et al, 2018;Yuliana dkk., 2020;Zebua dkk., 2019).…”
Section: Rancang Bangun Purwarupa Energy Harvesting Menggunakan Piezo...unclassified